Antarctic bacterial isolates that produce cold-active extracellular proteases at low temperature but are active and stable at high temperature - Martínez-Rosales, Cecilia; Castro-Sowinski, Susana (Polar Research, 2011)
We report the isolation and identification of bacteria that produce extracellular cold-active proteases, obtained from water samples collected near the Uruguayan Antarctic Base on King George Island, South Shetlands. The bacteria belonged to the genera Pseudomonas (growth between 4 and 30°C) and Flavobacterium (growth between 4 and 18°C). In all cases, extracellular protease production was evident when reaching the stationary phase at 18 and 4ºC, but was not detected at 30ºC. The zymogram revealed the secretion of one extracellular protease per isolate, each with different relative electrophoretic mobility. The extracellular proteases produced at 4ºC showed thermal activity and stability at 30ºC. Both activity and stability at temperature higher that 10ºC have no physiological meaning because the isolates do not experience such temperatures in the Antarctic environment; however, the possible ecological value of cold-active and -stable extracellular proteases is discussed. Keywords: Antarctic, cold-active enzymes, protease.
Keywords: Sørishavet; bakterier; biokjemi; marin biologi; oseanografi

Sydpolsekspedisjonen 1910-1914 - Nilsen, Thorvald (Frammuseet, 2011)
Publication Title: Frammuseet presenterer
Keywords: Antarktis; Fram (skip); Sydpolen; Sydpolsekspedisjonen; dagbøker; oppdagelsesreiser; oseanografi; polarområdene

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Resources for fish feed in future mariculture - Olsen, Yngvar (Aquaculture Environment Interactions, 2011)
There is a growing concern about the ability to produce enough nutritious food to feed the global human population in this century. Environmental conflicts and a limited freshwater supply constrain further developments in agriculture; global fisheries have levelled off, and aquaculture may have to play a more prominent role in supplying human food. Freshwater is important, but it is also a major challenge to cultivate the oceans in an environmentally, economically and energy-friendly way. To support this, a long-term vision must be to derive new sources of feed, primarily taken from outside the human food chain, and to move carnivore production to a lower trophic level. The main aim of this paper is to speculate on how feed supplies can be produced for an expanding aquaculture industry by and beyond 2050 and to establish a roadmap of the actions needed to achieve this. Resources from agriculture, fish meal and fish oil are the major components of pellet fish feeds. All cultured animals take advantage of a certain fraction of fish meal in the feed, and marine carnivores depend on a supply of marine lipids containing highly unsaturated fatty acids (HUFA, with ≥3 double bonds and ≥20 carbon chain length) in the feed. The availability of HUFA is likely the main constraint for developing carnivore aquaculture in the next decades. The availability of fish meal and oil will decrease, and the competition for plant products will increase. New harvested resources are herbivore zooplankton, such as Antarctic krill and red feed, and new produced resources are macroalgae, transgenic higher HUFA-producing plants and bacterial biomass. These products are to a limited extent components of the human food chain, and all these resources will help to move cultured carnivores to lower trophic levels and can thereby increase the production capacity and the sustainability of the production. Mariculture can only become as successful as agriculture in the coming century if carnivores can be produced at around Trophic Level 2, based mainly on plant resources. There is little potential for increasing the traditional fish meal food chain in aquaculture. KEYWORDS: Global aquaculture · Mariculture · Feed resources · Marine lipids · HUFA · Trophic level
Keywords: Sørishavet; alger; bakterier; biomasse; bioressurser; fiskeri; havbruksnæring; jordbruk; krill; marin biologi; marine planter; matproduksjon; oseanografi; zooplankton

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Near-surface eddy dynamics in the Southern Ocean - Trani, Marilisa; Falco, Pierpaolo; Zambianchi, Enrico (Polar Research, 2011)
The Antarctic Circumpolar Current (ACC) is a crucial component of the global ocean conveyor belt, acting as a zonal link among the major ocean basins but, to some extent, limiting meridional exchange and tending to isolate the ocean south of it from momentum and heat income. In this work we investigate one of the most important mechanisms contributing to the poleward transfer of properties in the Southern Ocean, that is the eddy component of the dynamics. For this particular purpose, observations obtained from near-surface drifters have been used: they represent a very useful data set to analyse the eddy field because of their ability to catch a large number of scales of motion while providing a quasi-synoptic coverage of the investigated area. Estimates of the eddy heat and momentum fluxes are carried out using data taken from the Global Drifter Program databank; they refer to Surface Velocity Program drifter trajectories collected in the area south of 358S between 1995 and 2006. Eddy kinetic energies, variance ellipses, momentum and heat fluxes have been calculated using the pseudo-Eulerian method, showing patterns in good agreement with those present in the literature based on observational and model data, although there are some quantitative differences. The eddy fluxes have been separated into their rotational and divergent portions, the latter being responsible for the meridional transports. The associated zonal and depth-exponentially integrated meridional heat transport exhibits values spanning over a range between -0.4 PW and -1.1 PW in the ACC region, consistent with previous estimates. Keywords: Antarctic Circumpolar Current; eddy fluxes; Global Drifter Program data; Lagrangian oceanography; Helmholtz decomposition.
Keywords: Sørishavet; havstrømmer; hydrografi; oseanografi; virvelstrømmer

ICE Fimbulisen - top to bottom: season 2 expedition field report - Tronstad ed., Stein; Polarinstitutt, Norsk (Norsk Polarinstitutt, 2011)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; logistikk; oseanografi